Epidemiology of invasive meningococcal disease and sequelae in the United Kingdom during the period 2008 to 2017 - a secondary database analysis - Sandra Guedes; Hélène Bricout; Edith Langevin; Sabine Tong; Isabelle Bertrand-Gerentes (BMC, 2022)
Abstract Background Invasive meningococcal disease (IMD) causes high fatality in untreated patients alongside long-term sequelae in 20% survivors. For a comprehensive assessment of epidemiology, an analysis of these sequelae is required. This study aims to investigate the epidemiology of disease between 2008 and 2017 including a description of the sequelae, through the analysis of data collected from the UK Clinical Practice Research Datalink (CPRD) linked with data from the Hospital Episode Statistics (HES), and Office for National Statistics (ONS) mortality registry data. Methods This was a 10-year retrospective observational cohort study designed to describe the incidence, case-fatality rate (CFR) and occurrence of sequelae due to meningococcal disease, in the UK between 2007 and 2017 using data from the UK CPRD-HES-ONS. Cases were identified and matched on age, gender, date of diagnosis of IMD and followed-up-time with a control group without IMD. Demographics, clinical characteristics, mortality, and IMD-related sequelae were examined for IMD cases and compared with matched controls for a more comprehensive assessment. Results The study analysed 640 IMD patients with majority of the cases diagnosed (76.9%) in a hospital setting. Age-group analysis showed a decrease in the incidence rate of IMD in patients aged <1 year (30.4 - 7.5%) and an increase in those >50 years (10.4 - 27.8%). CFR was slightly higher among females, toddlers, and adults >50 years. No significant change in CFR was observed over study period. Case-control study showed a higher number of IMD sequelae among cases compared to age- and gender-matched controls, especially in those ≥ 50 years. Conclusion The study showed that, despite a relatively low incidence rate, IMD is responsible for a high CFR, namely in older age groups and by a high number of IMD sequelae. The study showed that leveraging data from existing databases can be used to complement surveillance data in truly assessing the epidemiology of IMD. Despite the availability of routine vaccination programs, IMD still poses a significant burden in the healthcare system of the UK. Optimization of vaccination programs may be required to reduce the disease burden.